The relationship between microfilaraemic and amicrofilaraemic loiasis involving co-infection with Mansonella perstans and clinical symptoms in an exposed population from Gabon. Issue 4 (13th August 2015) - Bouyou Akotet, M.K.; Owono-Medang, M.; Mawili-Mboumba, D.P.; Moussavou-Boussougou, M.N.; Nzenze Afène, S.; Kendjo, E.; Kombila, M.
Abstract: The relationship between the frequency of loiasis objective symptoms and microfilaraemic or amicrofilaraemic infection was assessed in 1148 exposed patients also infected, or not, with Mansonella perstans . Filarial infections were detected by direct microscopy, leucoconcentration and serology, with prevalence values of 39.5% Loa loa, 5.6% M. perstans and 3.4% co-infection with both filarial species. Amicrofilaraemic or occult loiasis (OL) predominated among L. loa- infected individuals, with a prevalence of 58.2%. Hypermicrofilaraemia (>8000 microfilariae (mf)/ml) was found in 18.4% of L. loa microfilaraemic patients, with 25.7% of them harbouring more than 30, 000 mf/ml. Up to 34% of patients with OL showed evidence of Calabar swelling, compared with 26.3% of microfilaraemic patients ( P = 0.03). Overall 5.3% of patients presented with adult worm migration across the eye, representing 16.3% of microfilaraemic individuals and 11.4% of amicrofilaraemic patients ( P = 0.13). This symptom was similarly found in patients with more than 30, 000 mf/ml (22%), those with microfilaraemia between 8 and 30, 000 mf/ml (15.4%) and also in individuals with low or without microfilaraemia (16.1%) ( P = 0.7). Five (14.3%) hypermicrofilaraemic patients did not present any L. loa- specific objective symptoms, as well as all the patients with single M. perstans infection. The presence of adult eye worm migration as a strong predictor of high microfilaraemia density would obscure the real burden of L. loa hypermicrofilaraemia in exposed individuals. For epidemiological purposes and control strategies, the mapping of L. loa in endemic areas should also take into account the group of patients with occult loiasis.